Efficacy and safety profile of xanthines in COPD: a network meta-analysis. (2nd May 2018) - Cazzola, Mario; Calzetta, Luigino; Barnes, Peter J.; Criner, Gerard J.; Martinez, Fernando J.; Papi, Alberto; Gabriella Matera, Maria
Theophylline can still have a role in the management of stable chronic obstructive pulmonary disease (COPD), but its use remains controversial, mainly due to its narrow therapeutic window. Doxofylline, another xanthine, is an effective bronchodilator and displays a better safety profile than theophylline. Therefore, we performed a quantitative synthesis to compare the efficacy and safety profile of different xanthines in COPD. The primary end-point of this meta-analysis was the impact of xanthines on lung function. In addition, we assessed the risk of adverse events by normalising data on safety as a function of person-weeks. Data obtained from 998 COPD patients were selected from 14 studies and meta-analysed using a network approach. The combined surface under the cumulative ranking curve (SUCRA) analysis of efficacy (change from baseline in forced expiratory volume in 1 s) and safety (risk of adverse events) showed that doxofylline was superior to aminophylline (comparable efficacy and significantly better safety), bamiphylline (significantly better efficacy and comparable safety), and theophylline (comparable efficacy and significantly better safety). Considering the overall efficacy/safety profile of the investigated agents, the results of this quantitative synthesis suggest that doxofylline seems to be the best xanthine for the treatment of COPD. Doxofylline is an effective and safe xanthine for the treatment of COPD http://ow.ly/ApV330iXSXv